Medical corrosion-resistant high-magnification Teflon heat-shrinkable sleeve and preparation method thereof
Patent Information
- Application Number
- CN202611205251.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]针对现有医用铁氟龙热缩套管收缩倍率低、高倍率下耐蚀性差、功能层易剥落、生物功能不足的缺陷,本发明提供一种医用耐腐蚀高倍率铁氟龙热缩套管及其制备方法,实现超高径向收缩倍率的同时,兼具优异的耐腐蚀性、抗蠕变性与主动抗菌防血栓性能
1、本发明采用表面改性含氟羟基磷灰石与氟聚合物共混、结合辐照交联的基体方案,含氟羟基磷灰石可与聚四氟乙烯、全氟烷氧基树脂形成的三维交联网络互穿嵌合,借助纳米增强效应提升基体的结构稳定性、耐介质渗透性能与高温抗蠕变能力;同时通过调控交联密度保留高分子链段的高弹形变能力,使管材可实现大倍率径向收缩并保持优异的收缩回复精度,解决了传统铁氟龙热缩管高倍率化后力学性能与耐介质性能下降的技术问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of heat shrink tubing, specifically to a medical corrosion-resistant high-ratio Teflon heat shrink tubing and its preparation method. Background Technology
[0002] With the rapid development of interventional medicine and implantable devices, heat shrink tubing, as a core component for device encapsulation, insulation protection, and dimensional repair, faces stringent requirements regarding shrinkage ratio, media stability, and blood compatibility. Polytetrafluoroethylene (PTFE) and other Teflon materials have become the mainstream substrate for medical heat shrink tubing due to their excellent chemical corrosion resistance, temperature resistance, and bioinertness. However, existing technologies still have the following problems: First, it is difficult to balance shrinkage ratio and mechanical properties. Conventional PTFE heat shrink tubing, limited by its crystalline structure and cross-linking process, typically has a radial shrinkage ratio of 2-4:1, which cannot meet the high-ratio encapsulation requirements of small-sized interventional devices. Lowering the cross-linking degree to increase the ratio leads to a significant decrease in the tubing's creep resistance and stress crack resistance, making it prone to permanent deformation and leakage after long-term implantation or sterilization. Second, the surface functional layer is prone to failure under high-ratio deformation. Medical applications require heat shrink tubing to possess anti-fouling, antibacterial, and anti-thrombotic properties. Existing physically coated or weakly bonded functional layers tend to crack and peel off due to interfacial stress concentration during high shrinkage ratios (6:1 and above), resulting in a functional retention rate of less than 60%, which cannot meet the needs of long-term clinical use. Thirdly, interfacial bonding stability is poor. Some modification schemes directly graft functional layers onto the substrate surface, leading to significant differences in properties between the substrate and the surface layer. During high shrinkage ratios, interlayer shear stress easily triggers delamination failure, and there is a lack of effective interfacial buffering and anchoring structures.
[0003] Currently, there is a market demand for a Teflon heat shrink tubing that can simultaneously achieve high shrinkage ratio, high strength and corrosion resistance, medical-grade anti-fouling and antibacterial properties, and meet biocompatibility standards. Summary of the Invention
[0004] To address the shortcomings of existing medical Teflon heat shrink tubing, such as low shrinkage ratio, poor corrosion resistance at high shrinkage ratios, easy peeling of the functional layer, and insufficient biological function, this invention provides a medical corrosion-resistant high-ratio Teflon heat shrink tubing and its preparation method, achieving an ultra-high radial shrinkage ratio while possessing excellent corrosion resistance, creep resistance, and active antibacterial and antithrombotic properties.
[0005] The objective of this invention is achieved through the following technical solution: In a first aspect, the present invention provides a medical corrosion-resistant high-ratio Teflon heat shrink tubing, which comprises, from the inside out, a base tube layer, a cross-linked transition layer, and a surface biomimetic functional layer.
[0006] Furthermore, the matrix tube layer is formed by blending and crosslinking surface-modified fluorinated hydroxyapatite (F-HA), polytetrafluoroethylene (PTFE) resin, perfluoroalkoxy (PFA) resin, and crosslinking sensitizer triallyl isocyanurate (TAIC).
[0007] Furthermore, the raw material composition of the matrix tube layer, by mass parts, is as follows: Surface-modified fluorinated hydroxyapatite 2-8 parts; polytetrafluoroethylene resin 70-95 parts; perfluoroalkoxy resin 5-30 parts; triallyl isocyanurate 0.5-2 parts.
[0008] Furthermore, the polytetrafluoroethylene resin is a low molecular weight micro powder with a number average molecular weight of 50,000-150,000, a melt index of 1-10 g / 10 min (test conditions: 372℃, 10 kg), and an average particle size of 20-50 μm; the perfluoroalkoxy resin has a melt index of 15-30 g / 10 min (test conditions: 372℃, 5 kg), a melting point of 300-310℃, and a perfluoropropyl vinyl ether (PPVE) side chain molar content of 1.5%-3.0%.
[0009] Furthermore, the surface-modified fluorinated hydroxyapatite is nano-hydroxyapatite modified with a fluorinated silane coupling agent; the nano-hydroxyapatite is hexagonal, with a diameter of 20-50 nm, a length of 1-3 μm, and an aspect ratio ≥50.
[0010] Furthermore, the preparation method of the surface-modified fluorinated hydroxyapatite is as follows: 10g of nano-hydroxyapatite is dispersed in 100mL of 80wt% ethanol solution, 2-3g of trifluoropropyltriethoxysilane is added, and the mixture is treated under reflux for 12h. After centrifugation, washing and drying, the surface-modified fluorinated hydroxyapatite is obtained.
[0011] Furthermore, the thickness of the substrate tube layer is 85-90 μm; the crosslinking transition layer is a crosslinking layer formed on the outer surface of the substrate tube by directional electron beam irradiation, with a thickness of 10-15 μm; and the thickness of the surface biomimetic functional layer is 50-200 nm.
[0012] Furthermore, the biomimetic functional layer on the surface is formed by double-bond functionalized SNAP-POSS-MA block copolymer via thiol-olefin click grafting. Specifically: cage-like polysilsesquioxane (POSS) serves as an inorganic nanonucleus, forming mechanical interlocking and covalent bonds with the fluoropolymer network of the crosslinked transition layer, constituting nano-anchoring sites; zwitterionic segments of sulfobetaine (SBMA) form a dense hydration layer on the surface, achieving passive antifouling; and S-nitrosothiol (SNAP), as a nitric oxide donor, can stably and slowly release NO under physiological conditions, achieving active antibacterial and antithrombotic effects.
[0013] Furthermore, the preparation method of the double-bond functionalized SNAP-POSS-MA block copolymer includes the following steps: S1, POSS aminoSNAP modification: Eight-amino cage-type polysilsesquioxane was dissolved in dimethyl sulfoxide, and S-nitroso-N-acetylcysteine and a condensing agent were added. The reaction was carried out at room temperature for 18 h under nitrogen protection and in the dark. The SNAP-POSS-NH2 was obtained by dialysis purification. S2, Initiator Grafting: SNAP-POSS-NH2 was dissolved in tetrahydrofuran, and triethylamine was added as an acid-binding agent under ice bath. Acryloyl chloride was added dropwise for 4 hours to introduce double bonds, and 2-bromoisobutyryl bromide was added dropwise for 6 hours to introduce ATRP initiation sites. After purification, double bond functionalized SNAP-POSS-Br was obtained. S3. Block polymerization: Using SNAP-POSS-Br as an initiator, under the catalytic system of CuBr / pentamethyldiethylenetriamine, hydroxyethyl methacrylate (HEMA) is first polymerized to obtain SNAP-POSS-PHEMA-Br, and then sulfobetaine methacrylate (SBMA) is added to continue polymerization to obtain crude block copolymer. S4. Double bond capping and purification: The crude product was dissolved in N,N-dimethylformamide, potassium acrylate was added, and the mixture was stirred at 40°C for 12 h to convert the terminal bromine atoms into acrylate double bonds; the product was dialyzed through an ethanol-water mixture and freeze-dried to obtain a double bond functionalized block copolymer.
[0014] Preferably, in S1, the molar ratio of octaaminoPOSS to S-nitroso-N-acetylcysteine is 1:3-5.
[0015] Preferably, in S1, the condensing agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride.
[0016] Preferably, in S2, the molar ratio of SNAP-POSS-NH2, acryloyl chloride, 2-bromoisobutyryl bromide, and triethylamine is 1:1-2:2-4:4-7.
[0017] Preferably, in S3, the molar ratio of SNAP-POSS-Br, HEMA, and SBMA is 1:20:50-150.
[0018] Preferably, in S4, the molar amount of potassium acrylate is 5-10 times that of the SNAP-POSS-Br macromolecular initiator.
[0019] Secondly, the present invention provides a method for preparing the above-mentioned medical corrosion-resistant high-ratio Teflon heat shrink tubing, comprising the following steps: Step 1, Raw material blending and preform extrusion: Polytetrafluoroethylene resin, perfluoroalkoxy resin, triallyl isocyanurate, and surface-modified fluorinated hydroxyapatite are dry-blended evenly, cold-pressed preformed and then sintered at high temperature, and the preformed capillary is obtained by plunger extrusion. Step 2, High-rate inflation and overall cross-linking: The initial capillary is heated to a highly elastic state, and then radially inflated to the target rate by high-pressure gas and rapidly cooled for shaping; subsequently, it is subjected to high-energy electron beam overall irradiation and high-temperature treatment to obtain the substrate tube; Step 3, Directional shallow irradiation to construct the transition layer: The outer surface of the substrate tube is irradiated with a low-energy electron beam to form a cross-linked transition layer on the surface, which is then annealed for later use. Step 4, Surface activation and thiol introduction: The outer surface of the pipe is activated by plasma, and then thiol active sites are introduced on the surface through silanization reaction; Step 5, thiol-ene click grafting functional layer: Immerse the pipe in a treatment solution containing double bond functionalized block copolymer and photoinitiator, initiate the thiol-ene click reaction with ultraviolet light, graft the biomimetic functional layer, clean and dry to obtain a semi-finished product; Step 6, photochemical stabilization treatment: The semi-finished product is treated with a stabilizing solution and then dried to obtain the finished product.
[0020] Preferably, in step 1, the dry blending rate is 100-300 rpm, the temperature is 25-30℃, the sintering temperature is 330-340℃, and the sintering time is 2-4 h.
[0021] Preferably, in step 2, the blowing temperature is 315-325℃, the blowing pressure is 0.6-1.5MPa, the overall irradiation parameters are: electron beam energy 2.0-3.0MeV, total absorbed dose 60-100kGy, and the irradiation temperature for high-temperature treatment is 310-320℃.
[0022] Preferably, in step 3, the shallow irradiation parameters are: electron beam energy 0.15-0.25 MeV, total absorbed dose 120-180 kGy; annealing conditions are vacuum annealing at 60°C for 2 hours.
[0023] Preferably, in step 4, the plasma treatment uses a mixed gas with an oxygen-argon volume ratio of 8:2, a treatment power of 100-200W, and a treatment time of 3-5min; the silanization reaction uses a mercaptopropyltrimethoxysilane ethanol aqueous solution with a silane volume fraction of 2%-5% and a solution pH of 4.5-5.5.
[0024] Preferably, in step 5, the ultraviolet light wavelength is 365 nm and the surface light intensity is 10-20 mW / cm². 2 The reaction time is 15-30 min; the UV initiator is 2-hydroxy-2-methylphenylacetone.
[0025] The beneficial effects of this invention are as follows: 1. This invention employs a matrix scheme that combines surface-modified fluorinated hydroxyapatite with fluoropolymers and irradiation crosslinking. The fluorinated hydroxyapatite can interpenetrate and interlock with the three-dimensional crosslinked network formed by polytetrafluoroethylene and perfluoroalkoxy resin. The nano-reinforcement effect enhances the structural stability, resistance to media penetration, and high-temperature creep resistance of the matrix. At the same time, by controlling the crosslinking density, the high elastic deformation capability of the polymer chain segments is retained, enabling the tube to achieve large-scale radial shrinkage and maintain excellent shrinkage recovery accuracy. This solves the technical problem of decreased mechanical properties and media resistance after high-scale expansion of traditional Teflon heat shrink tubing.
[0026] 2. This invention constructs a cross-linked transition layer in situ on the surface of the substrate tube by directional shallow irradiation with a low-energy electron beam. This transition layer is a homogeneous integral structure with the substrate, without a clear phase interface. The degree of cross-linking gradually changes in the radial direction, which can gradually disperse and release the interfacial shear stress between the surface functional layer and the substrate during the shrinkage and recovery of the tube. This avoids interlayer cracking and peeling of the functional layer caused by stress concentration, significantly improves the bonding strength of the functional layer after multiple heat shrinkage cycles, and ensures the structural reliability of the product during long-term service.
[0027] 3. This invention utilizes a mercapto-ene click chemistry reaction to achieve covalent bonding between the biomimetic functional layer and the substrate, exhibiting high reaction selectivity and controllable grafting structure. Simultaneously, the functional layer uses cage-like polysilsesquioxane as an inorganic nano-core unit, which can form a dual anchoring effect of mechanical interlocking and chemical bonding with the surface cross-linked fluoropolymer network, significantly enhancing the interfacial bonding force between the functional layer and the substrate. Under high-rate shrinkage deformation, the functional layer can still maintain structural integrity without detachment, effectively solving the problems of weak adhesion and easy detachment of physical coating layers, as well as insufficient interfacial bonding durability of conventional grafting schemes.
[0028] 4. The biomimetic functional layer of this invention has both passive antifouling and active antibacterial and antithrombotic functions. The zwitterionic sulfobetaine segments can form a stable hydration barrier on the material surface through hydration, reducing the non-specific adhesion of blood proteins and platelets, thus achieving a passive antifouling effect. The S-nitrosothiol type nitric oxide donor can continuously and stably release nitric oxide under physiological conditions, actively inhibiting the colonization and proliferation of pathogens and regulating the coagulation process. The synergistic effect of the two can endow the tubing with excellent blood compatibility and antibacterial properties, meeting the long-term use requirements of interventional and implantable medical devices for surface biological properties. Detailed Implementation
[0029] The technical solution of the present invention is illustrated below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not preclude the existence of other method steps before or after the combined steps, or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention. Furthermore, unless otherwise stated, the numbering of each method step is merely a convenient tool for identifying each method step, and not for limiting the order of the method steps or defining the scope of the present invention. Changes or adjustments to their relative relationships, without substantially altering the technical content, should also be considered within the scope of the present invention.
[0030] To better understand the above technical solutions, exemplary embodiments of the present invention are described in more detail below. While exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the invention to those skilled in the art.
[0031] The present invention will be further described below with reference to the following embodiments.
[0032] Example 1 This embodiment prepares a medical-grade corrosion-resistant high-ratio Teflon heat shrink tubing with a radial shrinkage ratio of 6:1. The specific preparation process is as follows: Step 1: Raw material blending and preform extrusion: (1) Weigh the raw materials according to the following mass fractions: 2 parts of surface-modified fluorinated hydroxyapatite, 95 parts of low molecular weight PTFE micro powder (number average molecular weight 50,000, melt index 1g / 10min, average particle size 20μm), 5 parts of PFA resin (melt index 15g / 10min, melting point 300℃, PPVE side chain content 1.5mol%), and 0.5 parts of TAIC.
[0033] (2) Put all raw materials into a high-speed mixer, set the temperature to 25℃ and the speed to 150rpm, and dry mix for 15min until uniformly dispersed. Add the mixed powder into a cold press mold, and cold press it into a cylindrical blank under a pressure of 20MPa, holding the pressure for 10min. Put the blank into a muffle furnace, heat it to 330℃ at a rate of 2℃ / min, and sinter it at a constant temperature for 4h. After sintering, let it cool naturally to room temperature with the furnace to obtain the extruded blank.
[0034] (3) Load the billet into the plunger extruder, set the barrel temperature to 340℃ and the die head temperature to 345℃, control the plunger advance rate to 0.8mm / s, and after extrusion through the die, cool and shape it through the sizing sleeve to obtain the initial capillary; control the inner diameter of the initial capillary to 1.0mm and the wall thickness to about 110μm.
[0035] Step 2, High-ratio blowing and overall irradiation crosslinking: (1) The initial capillary tube is fed into the continuous blowing equipment. The tube is first heated to 315°C through the heating section, so that the tube is in the PTFE near melting point high elastic state. Then, high pressure nitrogen is introduced into the tube and the nitrogen pressure is controlled at 0.6MPa so that the tube is blown radially uniformly. When the tube is blown to an inner diameter of 6.0mm, it is quickly cooled and shaped by ice water bath to obtain an expanded diameter base tube. The expanded diameter base tube is kept under internal pressure and traction tension and quickly cooled and shaped by ice water bath to obtain a solid expanded diameter base tube with an inner diameter of 6.0mm.
[0036] (2) The expanded diameter base tube after cooling and shaping was placed in a high-energy electron accelerator for overall irradiation crosslinking under nitrogen protection at room temperature. The electron beam energy was set to 2.0 MeV, the total absorbed dose was 60 kGy, and the dose rate was 10 kGy / pass. The tube was irradiated back and forth until the total dose reached the target. After irradiation, the tube was placed in a muffle furnace and heated to 310°C at a rate of 2°C / min under nitrogen protection. The temperature was maintained for 30 min to eliminate residual free radicals and improve the degree of crosslinking. Then, the tube was cooled to room temperature with the furnace to obtain an overall crosslinked and morphologically fixed base tube.
[0037] Step 3: Constructing a transition layer through directional shallow irradiation: The substrate tube was fixed on a rotating fixture, and its outer surface was irradiated using a low-energy electron beam device. The electron beam energy was set to 0.15 MeV, and the total absorbed dose was 120 kGy. The uniform irradiation dose on the outer surface was ensured by controlling the tube rotation rate and scanning rate. After irradiation, the tube was placed in a vacuum drying oven and vacuum annealed at 60°C for 2 hours to eliminate internal stress, then removed for later use. Testing showed that the thickness of the cross-linked transition layer formed on the outer surface of the tube was approximately 10 μm.
[0038] Step 4, Surface activation and thiol group introduction: (1) Insert the annealed base tube into the cavity of the plasma treatment equipment, evacuate the vacuum, and introduce an argon-oxygen mixed gas (volume ratio 8:2). Control the total gas flow rate to 50 sccm and maintain the cavity pressure at 20 Pa. Set the plasma treatment power to 100 W and process continuously for 3 min to activate and etch the outer surface of the tube, introducing hydroxyl active sites.
[0039] (2) Prepare mercaptopropyltrimethoxysilane ethanol aqueous solution: the volume ratio of ethanol to deionized water is 9:1. Add glacial acetic acid to adjust the pH of the system to 4.5, then add mercaptopropyltrimethoxysilane, stir evenly and let stand for hydrolysis for 30 min. The final silane volume fraction is 2%.
[0040] (3) Immediately immerse the plasma-activated tube in the above silane solution at room temperature for 15 min, and then slowly pull it out of the liquid surface at a speed of 0.5 mm / s. After removal, place the tube in an oven at 110℃ for curing reaction for 1 h, so that the silanol groups and the hydroxyl groups on the tube surface can fully condense to form a stable -Si-O-Si- covalent bond and introduce thiol active sites. After the reaction is completed, remove the tube, rinse the surface with anhydrous ethanol 3 times, and dry it with nitrogen for later use.
[0041] Step 5: Click grafting of thiol-ene functional layer: (1) Preparation of functional layer treatment solution: Using ethanol as solvent, add the prepared double bond functionalized SNAP-POSS-MA block copolymer, stir until completely dissolved, and prepare a solution with a mass fraction of 5%; then add 2-hydroxy-2-methylphenylacetone, whose mass is 3% of the mass of the block copolymer, and stir evenly.
[0042] (2) Immerse the pipe with introduced thiol groups into the above treatment solution for 5 minutes to ensure the solution fully wets the pipe wall. Then fix it in a rotating fixture and place it in an ultraviolet light reaction chamber. Evacuate the reaction chamber and fill it with high-purity nitrogen gas, repeating this process three times to ensure the reaction is carried out under an inert atmosphere. Irradiate the pipe with a 365nm ultraviolet lamp, controlling the light intensity on the pipe surface to 10mW / cm². 2 During the irradiation process, the pipe rotates at a constant speed to ensure uniform light exposure. The total irradiation time is 15 minutes, which triggers the mercapto-ene click reaction.
[0043] (3) After the reaction was completed, the tube was removed and ultrasonically cleaned three times each with ethanol and deionized water for 5 minutes each time to remove the uncovalently bonded copolymer and residual initiator. The tube was then dried with nitrogen to obtain the semi-finished product. The thickness of the biomimetic functional layer on the surface was measured to be approximately 50 nm.
[0044] Step 6, Photochemical Stabilization Treatment: (1) Preparation of stabilization solution: Using phosphate buffer solution with pH=7.4 as solvent, add 0.1wt% 2,6-di-tert-butyl-p-cresol and 0.05wt% 2-hydroxy-4-methoxybenzophenone, and stir until homogeneous.
[0045] (2) Immerse the semi-finished product in the stabilization solution and soak it at 30°C in the dark for 2 hours. After the treatment, take out the pipe, rinse it with deionized water, and vacuum dry it under sterile conditions to obtain the finished heat shrink tubing.
[0046] In step 1 above, the preparation of surface-modified fluorinated hydroxyapatite (F-HA) includes: 10 g of hexagonal nano-hydroxyapatite whiskers (20 nm in diameter, 1 μm in length, aspect ratio 50) were added to a three-necked flask containing 100 mL of 80% ethanol aqueous solution and ultrasonically dispersed for 30 min until homogeneous. 2 g of trifluoropropyltriethoxysilane was added to the system, stirred until homogeneous, and then heated to 80 °C. The mixture was refluxed and reacted at this temperature for 12 h. After the reaction was complete, the mixture was cooled to room temperature and centrifuged at 8000 rpm for 10 min. The supernatant was discarded. The lower precipitate was washed three times with ethanol, centrifuged after each wash. The washed product was placed in a vacuum drying oven and dried under vacuum at 60 °C for 12 h. After grinding, it was sealed for later use.
[0047] In step 5 above, the preparation of the double-bond functionalized SNAP-POSS-MA block copolymer includes: SNAP modification of S1 and POSS amino groups 1 mmol of octaaminocage-type polysilsesquioxane (molecular weight 873.58) was dissolved in 50 mL of anhydrous dimethyl sulfoxide (DMSO) under nitrogen protection and stirred in the dark until completely dissolved. 3 mmol of S-nitroso-N-acetylcysteine and 3.6 mmol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added to the system, and nitrogen was continuously purged for 10 min to remove oxygen. The mixture was then sealed and stirred at room temperature in the dark for 18 h. After the reaction was complete, the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da and dialyzed against ethanol for 3 days, changing the dialysate every 12 h. After dialysis, the solution was freeze-dried to obtain SNAP-modified aminoPOSS (SNAP-POSS-NH2), which was then stored in the dark at low temperature.
[0048] S2, Preparation of macromolecular initiators Dissolve 1 mmol of the above SNAP-POSS-NH2 in 40 mL of anhydrous tetrahydrofuran (THF), cool to 0 °C in an ice bath, add 4 mmol of triethylamine as an acid-binding agent, and stir until homogeneous. Under nitrogen protection and in the dark, slowly add 10 mL of THF solution containing 1 mmol of acryloyl chloride over a period of 30 min. After the addition is complete, maintain the reaction temperature at 0 °C for 4 h. Subsequently, continue to slowly add 10 mL of THF solution containing 2 mmol of 2-bromoisobutyryl bromide over a period of 40 min. After the addition is complete, allow the temperature to rise naturally to room temperature and continue the reaction for 6 h. After the reaction is complete, filter to remove the triethylamine hydrochloride precipitate, add the filtrate to a large amount of ice-cold diethyl ether to precipitate, collect the precipitate by centrifugation, dissolve in THF and precipitate again in ice-cold diethyl ether, repeat the purification process 3 times. The final product is dried under vacuum to constant weight to obtain the double-bond functionalized SNAP-POSS-Br macromolecular initiator, which is stored at low temperature and protected from light.
[0049] S3, ATRP polymerization of block copolymers In a dry Schlenk reaction tube, 0.1 mmol of SNAP-POSS-Br macromolecular initiator, 2 mmol of hydroxyethyl methacrylate (HEMA), and 15 mL of N,N-dimethylformamide (DMF) were added and ultrasonically dispersed. 0.05 mmol of cuprous bromide and 0.05 mmol of pentamethyldiethylenetriamine were added to the system. After three cycles of freezing-vacuuming-nitrogen purging to remove oxygen, the tube was sealed and placed in a 40°C oil bath with stirring for 6 h to complete the first block polymerization. After the reaction was complete, 10 mL of a DMF solution containing 5 mmol of sulfobetaine methacrylate (SBMA) was rapidly injected into the system. The reaction was again subjected to three cycles of freezing-vacuuming-nitrogen purging, sealed, and placed in a 45°C oil bath to continue the reaction for 12 h to complete the second block polymerization. After the reaction was terminated, the reaction solution was exposed to air to quench the polymerization, and then precipitated by dropping into a large amount of ice-cold methanol. The crude product was collected by centrifugation to obtain crude SNAP-POSS-PHEMA-b-PSBMA-Br.
[0050] S4, terminal double bond end-capping modification The crude product was completely dissolved in 30 mL of LDM, stirred until fully dissolved, and 0.15 mmol of potassium acrylate was added. The mixture was heated to 40 °C and stirred under nitrogen protection in the dark for 12 h to replace the bromine atom at the end of the molecular chain with an acrylate double bond. After the reaction was completed, the reaction solution was dropped into ice-cold diethyl ether to precipitate the product, which was then collected by centrifugation. The product was dissolved in a small amount of ethanol and precipitated again, and this process was repeated twice.
[0051] S5. Dialysis purification and lyophilization The capped product was dissolved in a small amount of ethanol-water mixed solvent (volume ratio 1:1) and transferred to a dialysis bag with a molecular weight cutoff of 8000-14000 Da. Dialysis was performed for 3 days using the ethanol-water mixed solvent as the dialysis medium, with the dialysis solution being changed every 8 hours. After dialysis, the solution in the bag was collected, pre-frozen, and then freeze-dried for 48 hours to obtain the double-bond functionalized SNAP-POSS-MA block copolymer, which was then stored in a sealed container at low temperature and protected from light.
[0052] Example 2 This embodiment prepares a medical-grade corrosion-resistant high-ratio Teflon heat shrink tubing with a radial shrinkage ratio of 7:1. The specific preparation process is as follows: Step 1: Raw material blending and preform extrusion: (1) Weigh the raw materials according to the following mass fractions: 5 parts of surface-modified fluorinated hydroxyapatite (prepared as in Example 1), 82 parts of low molecular weight PTFE micro powder (number average molecular weight 100,000, melt index 5 g / 10 min (372 ℃ / 10 kg), average particle size 35 μm), 18 parts of PFA resin (melt index 22 g / 10 min (372 ℃ / 5 kg), melting point 305 ℃, PPVE side chain content 2.2 mol%), and 1.2 parts of TAIC.
[0053] (2) Put all raw materials into a high-speed mixer, set the temperature to 27℃ and the speed to 200rpm, and dry mix for 20min until evenly dispersed. Add the mixed powder into a cold press mold and cold press it into a cylindrical blank under a pressure of 25MPa for 12min. Place the blank in a muffle furnace and heat it to 335℃ at a rate of 2℃ / min, and sinter it at a constant temperature for 3h. After sintering, allow it to cool naturally to room temperature in the furnace to obtain the extruded blank.
[0054] (3) Load the billet into the plunger extruder, set the barrel temperature to 345℃ and the die head temperature to 350℃, control the plunger advance rate to 0.7mm / s, and after extrusion through the die, cool and shape it through the sizing sleeve to obtain the initial capillary; control the inner diameter of the initial capillary to 1.0mm and the wall thickness to about 112μm.
[0055] Step 2: High-ratio blow-up and overall irradiation crosslinking: (1) The initial state capillary tube is fed into the continuous blowing equipment. The tube is first heated to 320°C through the heating section, so that the tube is in the PTFE near melting point high elastic state. Then, high pressure nitrogen is introduced into the tube and the nitrogen pressure is controlled at 1.0 MPa so that the tube is blown radially uniformly. When the tube is blown to an inner diameter of 7.0 mm, it is quickly cooled and shaped by ice water bath to obtain an expanded diameter base tube. The expanded diameter base tube is kept under internal pressure and traction tension and quickly cooled and shaped by ice water bath to obtain a solid expanded diameter base tube with an inner diameter of 7.0 mm.
[0056] (2) The expanded diameter base tube after cooling and shaping was placed in a high-energy electron accelerator for overall irradiation crosslinking under nitrogen protection at room temperature. The electron beam energy was set to 2.5 MeV, the total absorbed dose was 80 kGy, and the dose rate was 10 kGy / pass. The tube was irradiated back and forth until the total dose reached the target. After irradiation, the tube was placed in a muffle furnace and heated to 330°C at a rate of 2°C / min under nitrogen protection. The temperature was kept constant for 30 min to eliminate residual free radicals and improve the degree of crosslinking. Then, the tube was cooled to room temperature with the furnace to obtain an overall crosslinked and morphologically fixed base tube.
[0057] Step 3: Constructing a transition layer using directional shallow irradiation: The substrate tube was fixed on a rotating fixture, and its outer surface was irradiated using a low-energy electron beam device. The electron beam energy was set to 0.20 MeV, and the total absorbed dose was 150 kGy. The uniform irradiation dose on the outer surface was ensured by controlling the tube rotation rate and scanning rate. After irradiation, the tube was placed in a vacuum drying oven and vacuum annealed at 60°C for 2 hours to eliminate internal stress, and then removed for later use. Cross-sectional micro-infrared or nanoindentation detection showed that the thickness of the cross-linked transition layer formed on the outer surface of the tube was approximately 12 μm.
[0058] Step 4: Surface activation and thiol group introduction: (1) Insert the annealed base tube into the cavity of the plasma treatment equipment, evacuate and then introduce argon-oxygen mixed gas (argon-oxygen volume ratio 8:2), control the total gas flow rate to 60 sccm, maintain the cavity pressure at 25 Pa, set the plasma treatment power to 150 W, and continuously process for 4 min to activate and etch the outer surface of the tube to introduce hydroxyl active sites.
[0059] (2) Prepare mercaptopropyltrimethoxysilane ethanol aqueous solution: the volume ratio of ethanol to deionized water is 9:1. Add glacial acetic acid to adjust the pH of the system to 5.0, then add mercaptopropyltrimethoxysilane, stir evenly and let stand for hydrolysis for 30 min so that the final volume fraction of silane is 3.5%.
[0060] (3) Immediately immerse the plasma-activated tube in the above silane solution at room temperature for 20 min, and then slowly pull it out of the liquid surface at a speed of 0.5 mm / s. After removal, place the tube in an oven at 110℃ for curing reaction for 1 h, so that the silanol groups and the hydroxyl groups on the tube surface can fully condense to form a stable -Si-O-Si- covalent bond and introduce thiol active sites. After the reaction is completed, remove the tube, rinse the surface with anhydrous ethanol 3 times, and dry it with nitrogen for later use.
[0061] Step 5: Click grafting of thiol-ene functional layer: (1) Preparation of functional layer treatment solution: Using ethanol as solvent, add double bond functionalized SNAP-POSS-MA block copolymer (prepared as in Example 1), stir until completely dissolved, and prepare a solution with a mass fraction of 7%; then add 2-hydroxy-2-methylphenylacetone, the mass of which is 3% of the mass of the block copolymer, and stir evenly.
[0062] (2) Immerse the pipe with introduced mercapto groups into the above treatment solution for 7 minutes to ensure the solution fully wets the pipe wall. Then fix it in a rotating fixture and place it in an ultraviolet light reaction chamber. Evacuate the reaction chamber and fill it with high-purity nitrogen gas, repeating this process three times to ensure the reaction is carried out under an inert atmosphere. Irradiate the pipe with a 365nm ultraviolet lamp and control the light intensity on the pipe surface to 15mW / cm. 2 During the irradiation process, the pipe rotates at a constant speed to ensure uniform light exposure. The total irradiation time is 22 minutes, which triggers the thiol-ene click reaction.
[0063] (3) After the reaction was completed, the tube was removed and ultrasonically cleaned three times each with ethanol and deionized water for 5 minutes each time to remove uncovalently bonded copolymers and residual initiators. The tube was then dried with nitrogen to obtain the semi-finished product. The thickness of the biomimetic functional layer on the surface was measured to be approximately 120 nm.
[0064] Step 6: Photochemical stabilization treatment: (1) Preparation of stabilization solution: Using phosphate buffer solution with pH=7.4 as solvent, add 0.1wt% 2,6-di-tert-butyl-p-cresol and 0.05wt% 2-hydroxy-4-methoxybenzophenone, and stir until homogeneous.
[0065] (2) Immerse the semi-finished product in the stabilization solution and soak it at 30°C in the dark for 2 hours. After the treatment, take out the pipe, rinse it with deionized water, and vacuum dry it under sterile conditions to obtain the finished heat shrink tubing.
[0066] Example 3 This embodiment prepares a medical-grade corrosion-resistant high-ratio Teflon heat shrink tubing with a radial shrinkage ratio of 8:1. The specific preparation process is as follows: Step 1: Raw material blending and preform extrusion: (1) Weigh the raw materials according to the following mass fractions: 8 parts of surface-modified fluorinated hydroxyapatite (prepared in the same way as in Example 1), 70 parts of low molecular weight PTFE micro powder (number average molecular weight 150,000, melt index 10 g / 10 min, average particle size 50 μm), 30 parts of PFA resin (melt index 30 g / 10 min, melting point 310 °C, PPVE side chain content 3.0 mol%), and 2 parts of TAIC.
[0067] (2) Put all raw materials into a high-speed mixer, set the temperature to 30℃ and the speed to 300rpm, and dry mix for 25min until uniformly dispersed. Add the mixed powder into a cold press mold, and cold press it into a cylindrical blank under a pressure of 30MPa, holding the pressure for 15min. Put the blank into a muffle furnace, heat it to 340℃ at a rate of 2℃ / min, and sinter it at a constant temperature for 2h. After sintering, let it cool naturally to room temperature with the furnace to obtain the extruded blank.
[0068] (3) Load the billet into the plunger extruder, set the barrel temperature to 350℃ and the die head temperature to 355℃, control the plunger advance rate to 0.6mm / s, and after extrusion through the die, cool and shape it through the sizing sleeve to obtain the initial capillary; control the inner diameter of the initial capillary to 1.0mm and the wall thickness to about 115μm.
[0069] Step 2: High-ratio blow-up and overall irradiation crosslinking: (1) The initial capillary tube is fed into the continuous blowing equipment. The tube is first heated to 325°C through the heating section, so that the tube is in the PTFE near melting point high elastic state. Then, high pressure nitrogen is introduced into the tube and the nitrogen pressure is controlled at 1.5MPa to make the tube expand radially uniformly. When the tube expands to an inner diameter of 8.0mm, it is quickly cooled and shaped by ice water bath to obtain an expanded diameter base tube. The expanded diameter base tube is kept under internal pressure and traction tension (to maintain its expanded shape) and quickly cooled and shaped by ice water bath to obtain a solid expanded diameter base tube with an inner diameter of 7.0mm.
[0070] (2) The expanded diameter base tube after cooling and shaping was placed in a high-energy electron accelerator for overall irradiation crosslinking under nitrogen protection at room temperature. The electron beam energy was set to 3.0 MeV, the total absorbed dose was 100 kGy, and the dose rate was 10 kGy / pass. The tube was irradiated back and forth until the total dose reached the target. After irradiation, the tube was placed in a muffle furnace and heated to 320°C at a rate of 2°C / min under nitrogen protection. The temperature was kept constant for 30 min to eliminate residual free radicals and improve the degree of crosslinking. Then, the tube was cooled to room temperature with the furnace to obtain an overall crosslinked and morphologically fixed base tube.
[0071] Step 3: Constructing a transition layer using directional shallow irradiation: The substrate tube was fixed on a rotating fixture, and its outer surface was irradiated using a low-energy electron beam device. The electron beam energy was set to 0.25 MeV, and the total absorbed dose was 180 kGy. The uniform irradiation dose on the outer surface was ensured by controlling the tube rotation rate and scanning rate. After irradiation, the tube was placed in a vacuum drying oven and vacuum annealed at 60°C for 2 hours to eliminate internal stress, then removed for later use. Testing showed that the thickness of the cross-linked transition layer formed on the outer surface of the tube was approximately 15 μm.
[0072] Step 4: Surface activation and thiol group introduction: (1) Insert the annealed base tube into the cavity of the plasma treatment equipment, evacuate the vacuum, and introduce an argon-oxygen mixed gas (volume ratio 8:2). Control the total gas flow rate to 70 sccm and maintain the cavity pressure at 30 Pa. Set the plasma treatment power to 200 W and process continuously for 5 min to activate and etch the outer surface of the tube, introducing hydroxyl active sites.
[0073] (2) Prepare mercaptopropyltrimethoxysilane ethanol aqueous solution: the volume ratio of ethanol to deionized water is 9:1. Add glacial acetic acid to adjust the pH of the system to 5.5, then add mercaptopropyltrimethoxysilane, stir evenly and let stand for hydrolysis for 30 min. The final silane volume fraction is 5%.
[0074] (3) Immediately immerse the plasma-activated tube in the above silane solution at room temperature for 20 min, and then slowly pull it out of the liquid surface at a speed of 0.5 mm / s. After removal, place the tube in an oven at 110℃ for curing reaction for 1 h, so that the silanol groups and the hydroxyl groups on the tube surface can fully condense to form a stable -Si-O-Si- covalent bond and introduce thiol active sites. After the reaction is completed, remove the tube, rinse the surface with anhydrous ethanol 3 times, and dry it with nitrogen for later use.
[0075] Step 5: Click grafting of thiol-ene functional layer: (1) Preparation of functional layer treatment solution: Using ethanol as solvent, add double bond functionalized SNAP-POSS-MA block copolymer (prepared as in Example 1), stir until completely dissolved, and prepare a solution with a mass fraction of 10%; then add 2-hydroxy-2-methylphenylacetone, the mass of which is 3% of the mass of the block copolymer, and stir evenly.
[0076] (2) Immerse the pipe with introduced thiol groups into the above treatment solution for 10 minutes to ensure the solution fully wets the pipe wall. Then fix it in a rotating fixture and place it in an ultraviolet light reaction chamber. Evacuate the reaction chamber and fill it with high-purity nitrogen gas, repeating this process three times to ensure the reaction is carried out under an inert atmosphere. Irradiate the pipe with a 365nm ultraviolet lamp, controlling the light intensity on the pipe surface to 20mW / cm². 2 During the irradiation process, the pipe rotates at a constant speed to ensure uniform light exposure. The total irradiation time is 30 minutes, which triggers the thiol-ene click reaction.
[0077] (3) After the reaction was completed, the tube was removed and ultrasonically cleaned three times each with ethanol and deionized water for 5 minutes each time to remove the uncovalently bonded copolymer and residual initiator. The tube was then dried with nitrogen to obtain the semi-finished product. The thickness of the biomimetic functional layer on the surface was measured to be approximately 200 nm.
[0078] Step 6: Photochemical stabilization treatment: (1) Preparation of stabilization solution: Using phosphate buffer solution with pH=7.4 as solvent, add 0.1wt% 2,6-di-tert-butyl-p-cresol and 0.05wt% 2-hydroxy-4-methoxybenzophenone, and stir until homogeneous.
[0079] (2) Immerse the semi-finished product in the stabilization solution and soak it at 30°C in the dark for 2 hours. After the treatment, take out the pipe, rinse it with deionized water, and vacuum dry it under sterile conditions to obtain the finished heat shrink tubing.
[0080] Comparative Example 1 (without F-HA enhancement) The only difference from Example 2 is that the surface-modified F-HA is not added to the matrix formulation, while the other raw material ratios and preparation process parameters are exactly the same as in Example 2.
[0081] Comparative Example 2 (without surface cross-linking layer) The only difference from Example 2 is that the surface cross-linking layer construction process in step 3 is omitted, and the subsequent activation and grafting are carried out directly on the surface of the overall cross-linked matrix tube obtained in step 2. All other parameters are exactly the same.
[0082] Comparative Example 3 (Physically Coated Functional Layer) The only difference from Example 2 is that: no surface thiolation and thiol-ene click reaction are performed. Instead, the pipe is directly immersed in a block copolymer ethanol solution of the same concentration as in Example 2. After immersion, it is taken out and dried at room temperature to form a physically coated functional layer. The rest of the substrate preparation process is the same as in Example 2.
[0083] Comparative Example 4 (Commercially available ordinary medical PTFE heat shrink tubing) Commercially available ordinary medical PTFE heat shrink tubing with a nominal shrinkage ratio of 4:1, without surface functional modification, was selected as a blank control.
[0084] Performance test results The shrinkage properties, mechanical corrosion resistance, interfacial bonding properties, and biological functions of the samples obtained in Example 2 and Comparative Examples 1-4 were tested, and the results are shown in the table below:
[0085] Examples 2 all achieved a high shrinkage ratio of 7 times while maintaining excellent creep resistance and body fluid resistance, verifying the synergistic enhancement effect of F-HA nanocrystals and cross-linked networks. In Comparative Example 1, the absence of F-HA significantly increased high-temperature permanent deformation and mass change rate. It was also observed that the cross-linked transition layer effectively released interfacial shear stress during high-ratio shrinkage; in Comparative Example 2 without the transition layer, the functional layer bonding strength significantly decreased after repeated shrinkage. Furthermore, it was shown that the thiol-ene covalently grafted POSS had a good anchoring effect, enabling the coating of Example 1 to achieve a cross-link rating of 0, far superior to the physical coating scheme of Comparative Example 3; the biological function retention rate was high after repeated shrinkage, demonstrating excellent long-term effectiveness. In addition, the synergistic effect of passive antifouling by zwitterions and active antibacterial properties by sustained-release NO achieved excellent anti-protein adhesion and antibacterial effects, meeting the requirements for use in blood contact medical devices.
[0086] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. The illustrative expressions of the above terms in this specification should not be construed as necessarily referring to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. In addition, those skilled in the art can combine and integrate the different embodiments or examples described in this specification.
[0087] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A medical corrosion-resistant high-ratio Teflon heat shrink tubing, characterized in that, From the inside out, it consists of a matrix tubular layer, a cross-linked transition layer, and a surface biomimetic functional layer; The matrix tube layer is formed by blending and crosslinking surface-modified fluorinated hydroxyapatite, polytetrafluoroethylene resin, perfluoroalkoxy resin, and crosslinking sensitizer triallyl isocyanurate. The cross-linked transition layer is a cross-linked layer formed on the outer surface of the matrix tube layer by directional electron beam irradiation; The surface biomimetic functional layer is formed by grafting a double-bond functionalized SNAP-POSS-MA block copolymer onto the surface of the crosslinked transition layer via a thiol-ene click reaction.
2. The medical corrosion-resistant high-ratio Teflon heat shrink tubing according to claim 1, characterized in that, The raw material composition of the matrix tube layer, by mass parts, is as follows: Surface-modified fluorinated hydroxyapatite 2-8 parts; polytetrafluoroethylene resin 70-95 parts; perfluoroalkoxy resin 5-30 parts; triallyl isocyanurate 0.5-2 parts.
3. The medical corrosion-resistant high-ratio Teflon heat-shrink tubing according to claim 1 or 2, characterized in that, The polytetrafluoroethylene resin is a low molecular weight micro powder with a number average molecular weight of 50,000-150,000, a melt index of 1-10 g / 10 min at 372℃ and 10 kg, and an average particle size of 20-50 μm. The perfluoroalkoxy resin has a melt index of 15-30 g / 10 min at 372℃ and 5 kg, a melting point of 300-310℃, and a perfluoropropyl vinyl ether side chain molar content of 1.5%-3.0%.
4. The medical corrosion-resistant high-ratio Teflon heat shrink tubing according to any one of claims 1-3, characterized in that, The surface-modified fluorinated hydroxyapatite is nano-hydroxyapatite modified with a fluorinated silane coupling agent; the nano-hydroxyapatite is hexagonal, with a diameter of 20-50 nm, a length of 1-3 μm, and an aspect ratio ≥50.
5. The medical corrosion-resistant high-ratio Teflon heat shrink tubing according to claim 4, characterized in that, The preparation method of the surface-modified fluorinated hydroxyapatite is as follows: 10g of nano-hydroxyapatite is dispersed in 100mL of 80wt% ethanol solution, 2-3g of trifluoropropyltriethoxysilane is added, and the solution is treated under reflux for 12h. After centrifugation, washing and drying, the surface-modified fluorinated hydroxyapatite is obtained.
6. The medical corrosion-resistant high-ratio Teflon heat shrink tubing according to any one of claims 1-5, characterized in that, The thickness of the substrate tube layer is 85-90 μm; the thickness of the crosslinking transition layer is 10-15 μm; and the thickness of the surface biomimetic functional layer is 50-200 nm.
7. The medical corrosion-resistant high-ratio Teflon heat shrink tubing according to any one of claims 1-6, characterized in that, In the biomimetic functional layer of the surface, cage-shaped polysilsesquioxane serves as an inorganic nanonucleus, forming mechanical interlocking and covalent bonding with the fluoropolymer network of the cross-linked transition layer, thus constituting nano-anchoring sites; sulfobetaine zwitterionic segments form a dense hydration layer on the surface; and S-nitrosothiol serves as a nitric oxide donor, which can slowly release nitric oxide under physiological conditions.
8. The medical corrosion-resistant high-ratio Teflon heat shrink tubing according to any one of claims 1-7, characterized in that, The preparation method of the double bond functionalized SNAP-POSS-MA block copolymer includes the following steps: S1, POSS aminoSNAP modification: Eight-amino cage-type polysilsesquioxane was dissolved in dimethyl sulfoxide, and S-nitroso-N-acetylcysteine and a condensing agent were added. The reaction was carried out at room temperature for 18 h under nitrogen protection and in the dark. The SNAP-POSS-NH2 was obtained by dialysis purification. S2, Initiator Grafting: SNAP-POSS-NH2 was dissolved in tetrahydrofuran, and triethylamine was added as an acid-binding agent under ice bath. Acryloyl chloride was added dropwise for 4 hours to introduce double bonds, and 2-bromoisobutyryl bromide was added dropwise for 6 hours to introduce ATRP initiation sites. After purification, double bond functionalized SNAP-POSS-Br was obtained. S3. Block polymerization: Using SNAP-POSS-Br as an initiator, under the catalytic system of CuBr / pentamethyldiethylenetriamine, hydroxyethyl methacrylate is first polymerized to obtain SNAP-POSS-PHEMA-Br, and then sulfobetaine methacrylate is added to continue polymerization to obtain crude block copolymer. S4. Double bond capping and purification: The crude product was dissolved in N,N-dimethylformamide, potassium acrylate was added, and the mixture was stirred at 40°C for 12 h to convert the terminal bromine atoms into acrylate double bonds; the product was dialyzed through an ethanol-water mixture and freeze-dried to obtain a double bond functionalized block copolymer.
9. The medical corrosion-resistant high-ratio Teflon heat shrink tubing according to claim 8, characterized in that, In S1, the molar ratio of octaaminocage-type polysilsesquioxane to S-nitroso-N-acetylcysteine is 1:3-5; in S1, the condensing agent is 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride; in S2, the molar ratio of SNAP-POSS-NH2, acryloyl chloride, 2-bromoisobutyryl bromide, and triethylamine is 1:1-2:2-4:4-7; in S3, the molar ratio of SNAP-POSS-Br, hydroxyethyl methacrylate, and sulfobetaine methacrylate is 1:20:50-150; in S4, the molar amount of potassium acrylate is 5-10 times that of the macromolecular initiator SNAP-POSS-Br.
10. A method for preparing a medical corrosion-resistant high-ratio Teflon heat-shrink tubing according to any one of claims 1-9, characterized in that, Includes the following steps: Step 1, Raw material blending and preform extrusion: Polytetrafluoroethylene resin, perfluoroalkoxy resin, triallyl isocyanurate, and surface-modified fluorinated hydroxyapatite are dry-blended evenly, cold-pressed preformed and then sintered at high temperature, and the preformed capillary is obtained by plunger extrusion. Step 2, High-rate inflation and overall cross-linking: The initial capillary is heated to a highly elastic state, and then radially inflated to the target rate by high-pressure gas and rapidly cooled for shaping; subsequently, it is subjected to high-energy electron beam overall irradiation and high-temperature treatment to obtain the substrate tube; Step 3, Directional shallow irradiation to construct the transition layer: The outer surface of the substrate tube is irradiated with a low-energy electron beam to form a cross-linked transition layer on the surface, which is then annealed for later use. Step 4, Surface activation and thiol introduction: The outer surface of the pipe is activated by plasma, and then thiol active sites are introduced on the surface through silanization reaction; Step 5, thiol-ene click grafting functional layer: Immerse the pipe in a treatment solution containing double bond functionalized block copolymer and photoinitiator, initiate the thiol-ene click reaction with ultraviolet light, graft the biomimetic functional layer, clean and dry to obtain a semi-finished product; Step 6, photochemical stabilization treatment: The semi-finished product is treated with a stabilizing solution and then dried to obtain the finished product.